Factors affecting instructors’ adoption of learning management systems: The case of Palestine - Abdallah, Nahel A. O.; Ahlan, Abdul Rahman; Abdullah, Odeh (Little Lion Scientific, 2019)
Although web-based learning systems are emerging as a useful tool for facilitating teaching and learning activities, instructors’ use of learning management systems in higher educational institutions is still limited. In this context, this empirical research investigates factors that can potentially contribute to learning management system adoption in Palestinian institutions of higher education. In addition, the study also developed an integrated model of instructor adoption of learning management systems by incorporating existing literature and multiple empirically verified theories, including the technology acceptance model and DeLone and McLean’s information system success model. Survey data collected from 365 university instructors were examined to evaluate the influence of various constructs on lecturers’ adoption of learning management systems using structural equation modeling. The research results show that perceived usefulness, perceived ease of use, system quality, information quality, service quality, management support, resistant to change, personnel IT innovativeness, attitude toward the system, computer efficacy and subjective norms influence instructors’ intention to use learning management systems. Findings of this research will be valuable for academicians and practitioners in implementation, management and continuous improvement of learning management systems.